Information and communication technologies and economic institutions - Akıncı, Atakan (My University, 2016)
In the 18th century The Industrial Revolution has enabled to develop and deployment of science and technology (S & T). Then, the world has faced with an unprecedented picture after the Revolution which was one of the breaking points in the entire history of the world. In the 20th century, the importance of S & T has increased dramatically. Science-based technology, especially ICT, has been very significant within the framework of economic development, sustainability of economic growth, and competitiveness. It is not possible to reject the effects of ICT on relationships among individuals, institutions and between them, as well as on the processes of production and distribution, management structures, the role of governments in innovations and industry, determining the policies of science, technology, and innovation. The progresses in ICT, especially in telecommunications technologies, and transition to information society have been observed in the world. In the second half of the 20th century, the effects of ICT on institutions have been one of the prominent topics in terms of the transformation in the world and Turkey especially In this study, the brief history of ICT is overviewed with its place in the world by referring to its effects in the extended introduction. In the second part, I explain the theoretical perspective on technology. Then in the third part, the relationship between ICT and economic institutions is viewed. In the next part, ICT sector situation in the world and Turkey, and some selected economic institutions in Turkey are observed to show ICT effects on. Last part is conclusion which includes some policy recommendations.

18. yüzyılda yaşanan Sanayi Devrimi, bilim ve teknolojinin gelişmesinde ve yayılmasında etkili oldu. Dünya tarihinin de kırılma noktalarından biri olan bu devrimden sonra, dünya daha önce görülmemiş bir tabloyla karşı karşıya kaldı. 20. yüzyılda ise bilim ve teknolojinin önemi çarpıcı bir biçimde arttı. Ekonomik kalkınma, ekonomik büyümenin sürdürülebilirliği ve rekabet gücü açısından bilim ve teknolojinin birbirine yakınlaşması önemli olmuştur. Ayrıca, son yıllarda Bilgi ve İletişim Teknolojileri (BİT) oldukça dikkat çekmektedir. Kişilerin ve kurumların hem kendi ilişkileri hem de birbirleri ile ilişkileri, üretim ve dağıtım süreçleri, yönetim yapıları, hükumetlerin inovasyon ve sanayideki rolleri, bilim, teknoloji ve sanayi politikaları üzerinde BİT’lerin etkisini reddetmek imkansızdır. Özellikle telekomünikasyon teknolojilerinde, yaşanan ilerlemeler ile birlikte dünyada Bilgi Toplumuna doğru büyük bir geçiş gözlemlenmektedir. 20. yüzyılın ikinci yarısında BİT’lerin kurumlar üzerindeki etkileri, dünyada ve Türkiye’de yaşanan dönüşüm açısından öne çıkan konulardan biri olmuştur. Bu çalışmada, öncelikle BİT’lerin dünyadaki yerini görmek için BİT’lerin etkilerine değinerek BİT’lerin tarihi gözden geçirilmiştir. İkinci bölümde, teknoloji üzerine teorik perspektif ele alınmıştır. Üçüncü bölümde BİT ve ekonomik kurumlar ilişkisinden bahsedilmektedir. Sonraki bölümde, dünyada ve Türkiye’de BİT sektörü incelenerek, BİT’lerin kurumlar üzerindeki etkilerini göstermek üzere, Bankalar ve Borsa İstanbul gibi Türkiye’deki bazı ekonomik kurumlar ele alınmıştır. Sonuç bölümünde ise bazı politika önerileri yer almaktadır.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2016
Keywords: Information and communications technology; Economic institutions; Economic growth and development; Technology and innovation; Bilgi ve iletişim teknolojileri; Ekonomik kurumlar; Büyüme ve kalkınma; Teknoloji ve inovasyon